2017
DOI: 10.1186/s40164-017-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of functional elements enhances the antitumor capacity of CAR T cells

Abstract: As chimeric antigen receptor (CAR) T cells have displayed an unprecedented efficacy in the treatment of CD19-positive malignances, it is believed that this cell therapy will be a milestone in the history of mankind’s conquering of cancer. However, there are some issues that restrict CAR T cells from reaching their optimal anti-tumor capacity, especially in the treatment of solid tumors. Inhibitory cytokines, immune checkpoint molecules, hypoxia and other adverse factors have been reported to be involved in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Notably, 1928zT2 T cells used in this study were incorporated with TLR2 domain, which showed improved anti-leukemia efficacy of CARs [ 12 , 22 ]. These 1928zT2 T cells not only could eradicate the CD19-expressing NALM6 cells and K562 cells specifically and potently in vitro, they could significantly promote the remission of NALM-6 subcutaneous tumors ex vivo, indicating the TLR2 incorporation enhanced the anti-leukemia effects of CAR T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 1928zT2 T cells used in this study were incorporated with TLR2 domain, which showed improved anti-leukemia efficacy of CARs [ 12 , 22 ]. These 1928zT2 T cells not only could eradicate the CD19-expressing NALM6 cells and K562 cells specifically and potently in vitro, they could significantly promote the remission of NALM-6 subcutaneous tumors ex vivo, indicating the TLR2 incorporation enhanced the anti-leukemia effects of CAR T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAR-T and TCR-T cell therapy makes use of functionally active T cells isolated from patients. These T cells are reconstructed and expanded ex vivo to recognize specific antigens on target cells and are now widely trialed to treat leukemia, lymphoma, and several solid tumors [ 52 58 ]. However, there are functional challenges of engineered T cell therapy in regard to T cell senescence and exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…CAR T cells are produced by inserting specific CAR genes via viral vectors into autologous or allogeneic T cells [ 42 ]. New-generation CARs have two or more co-stimulatory domains (e.g., 4-1BB, OX 40) that boost the stimulatory signal [ 43 , 44 ]. Anti-CD19 CAR T cells were recently FDA-approved for B-ALL in pediatric and young adult population [ 45 ].…”
Section: Chimeric Antigen Receptor (Car) T Cellsmentioning
confidence: 99%